Regulatory T Cell Subsets in Filarial Infection and Their Function - Metenou, Simon; Nutman, Thomas (Frontiers in Immunology, 2013)
Filarial infections in humans are chronic infections that cause significant morbidity. The chronic nature of these infections with continuous antigen release is associated with a parasite-specific T cell hypo-responsiveness that may over time also affect the immune responses to bystander antigens. Previous studies have shown the filarial parasite antigen-specific T cells hypo-responsiveness is mediated by regulatory cytokines -- IL-10 and TGF-β in particular. Recent studies have suggested that the modulated/regulated T cell responses associated with patent filarial infection may reflect an expansion of regulatory T cells (Tregs) that include both Tregs induced in peripheral circulation or pTregs and the thymus-derived Tregs or tTregs. Although much is known about the phenotype of these regulatory populations, the mechanisms underlying their expansion and their mode of action in filarial and other infections remain unclear. Nevertheless there are data to suggest that while many of these regulatory cells are activated in an antigen-specific manner the ensuing effectors of this activation are relatively non-specific and may affect a broad range of immune cells. This review will focus on the subsets and function of regulatory T cells in filarial infection.